Digital Media-Based Health Promotion at RSIA Aisyiyah Samarinda: Implementation of the Precede-Proceed Model - Salsabila Putri Balqis; Alifani Siti Nurilimi; Alya; Syaima Andrea Suci Ramadhani; Mohammad Fikri (Preventif : Jurnal Kesehatan Masyarakat, 2026)
Health promotion in hospitals is an important component of health services that emphasizes not only curative and rehabilitative efforts, but also promotive and preventive approaches. At RSIA 'Aisyiyah Samarinda, the implementation of health promotion still faces several challenges, including the suboptimal use of digital media as a tool for health education, gaps in health information among patients and their families, and the frequent occurrence of minor illnesses such as common cold and Acute Respiratory Infections (ARI). In addition, the utilization of digital health services, such as the Mobile JKN application, remains limited due to a lack of public understanding regarding its functions and benefits. This study aims to design, implement, and evaluate a digital media-based health promotion program at RSIA 'Aisyiyah Samarinda using the Precede–Proceed framework with a qualitative descriptive approach through a field study.  The research stages included field orientation, identification of common health problems, program planning using the SMART principle within a Plan of Action (POA), implementation through Instagram, and evaluation covering process, impact, and outcomes. The program is scheduled to be implemented in September 2025, focusing on health education related to common cold, ARI, and the use of the Mobile JKN application. The results indicate that Instagram effectively reaches a broader audience and increases engagement. Evaluations show improved health knowledge, short-term behavior changes, and better understanding of digital health services, highlighting its effectiveness in hospital-based health promotion.